Faktor – Faktor yang Mempengaruhi Kepuasan Pengguna Sistem Informasi Pengelolaan Keuangan Daerah (SIPKD) pada Kalangan Pegawai Negeri Sipil - Ready Wicaksono; Mispiyanti Mispiyanti (Universitas Trunojoyo Madura, 2019)
The Regional Financial Management Information System is an application developed by the Ministry of Home Affairs Directorate General of Regional Finance in the context of accelerating data transfer and efficiency in collecting regional financial data. One important aspect of utilizing the Regional Financial Management Information System is understanding the factors that influence the satisfaction of users of the Regional Financial Management Information System. This study regarding the use of SIPKD within the framework of the TAM theory and the Delone and Mclean Model (2003) to find out whether the system quality, information quality, service quality, infrastructure factors, and self-efficacy affect the satisfaction of SIPKD users. The Data collection method used in this study is a survey method by distributing questionnaires to respondents. The better the quality of the system, it will provide accurate and relevant quality information so that it helps the SIPKD users make the right decision. The services provided are of high quality and supported by the process of providing maximum internet connection infrastructure and facilities to provide SIPKD user satisfaction. Employees who use SIPKD have high self-efficacy. System quality, information quality, service quality, technological infrastructure factors, self-efficacy have a positive effect on SIPKD user satisfaction.